2021
DOI: 10.1182/bloodadvances.2020003749
|View full text |Cite
|
Sign up to set email alerts
|

Safety and reactogenicity of the recombinant zoster vaccine after allogeneic hematopoietic cell transplantation

Abstract: Allogeneic hematopoietic cell transplantation (HCT) recipients are at increased risk for varicella zoster virus (VZV) reactivation and associated complications. A nonlive adjuvanted recombinant zoster vaccine (RZV) has been developed to prevent herpes zoster (HZ), but there are no recommendations for use in this population. In this single-center prospective observational cohort study, we assessed the safety and reactogenicity of RZV, as well as incidence of graft-versus-host disease (GVHD) and confirmed cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…A study published by Natori, et al reported an incidence of new or worsening GVHD in about approximately 26% of patients who received the influenza vaccine but did not have a comparator group 21 . Baumrin, et al analyzed the effect of the recombinant zoster vaccine on GVHD incidence and concluded no significant difference 22 . We also observed few cases of eosinophilia, and hepatic impairment that occurred after the vaccination, however, it is difficult to ascribe causality to the vaccines due to the retrospective nature of this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study published by Natori, et al reported an incidence of new or worsening GVHD in about approximately 26% of patients who received the influenza vaccine but did not have a comparator group 21 . Baumrin, et al analyzed the effect of the recombinant zoster vaccine on GVHD incidence and concluded no significant difference 22 . We also observed few cases of eosinophilia, and hepatic impairment that occurred after the vaccination, however, it is difficult to ascribe causality to the vaccines due to the retrospective nature of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is not suitable to define if vaccination in allogeneic HSCT recipients was protective, because this warrants a larger study cohort and a placebo control group. However, a previous study on allogeneic HSCT recipients determined the rate of shingles following two doses of Shingrix™ [ 28 ]. The authors described that 3 out of 150 patients suffered from shingles (28.3/1000 person-years); which appears as low as compared to 41% of VZV reactivations at a median of 227 days (range 45–346 days) post-transplantation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…While smaller studies showed that RZV (administered at a median 8–9 months post-transplant) was also well-tolerated in allogenic HSCT recipients, it was less immunogenic than in autologous HSCT recipients. 31 , 32 However, administration of RZV before full immune reconstitution as well as its efficacy are yet to be evaluated in allogenic HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%